Remark: Long‐Distance Reflexives, Blocking Effects, and the Structure of Mandarin Comparatives. (March 2015) - Hsieh, I‐Ta Chris
Abstract Drawing on data concerning the long‐distance dependency of the Mandarin bare reflexive ziji 'self' in embedded comparatives, this remark compares two types of analyses of Mandarin comparatives—the Reduction Analysis and the Direct Analysis. The discussion shows that the long‐distance dependency of ziji in an embedded comparative can be easily captured in the Reduction Analysis, where a deletion operation is involved in the derivation; however, the Direct Analysis, where the constituent size of the standard of comparison is transparent, encounters challenges when facing the same data.